Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Guru - Julikha , Putri; Suratno, Eddy; Paul Karolus Pasaribu, Johni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The purpose of this study was to determine the effect of leadership style and work motivation on the performance of teachers at SMP Negeri 9 Jambi City. This research was conducted at SMP Negeri 9 Jambi City. The sample size was 55 respondents. Data were collected through interviews (interviews), questionnaires (questionnaires), and observation (observation) and using data analysis techniques with classical assumption methods, namely validity tests, reliability tests, multicolonierity tests, and heteroscedasticity tests. Based on the results of the analysis, it is found that leadership style and work motivation have a positive and significant effect on teacher performance. Then it was also found that there was a simultaneous and significant influence where the influence of leadership style and work motivation together could affect the improvement of teacher performance.